2014
DOI: 10.1093/aje/kwu158
|View full text |Cite|
|
Sign up to set email alerts
|

Joint Association of Genome-Wide Association Study-Identified Susceptibility Loci and Dietary Patterns in Risk of Renal Cell Carcinoma Among Non-Hispanic Whites

Abstract: Dietary factors may affect risk of renal cell carcinoma (RCC). In an ongoing case-control study of RCC initiated in Houston, Texas, in 2002, we identified 3 empirically derived dietary patterns: "fruits and vegetables," "American/Western," and "Tex-Mex." Among 659 RCC cases and 699 controls, we evaluated associations of these dietary patterns with RCC risk and whether the associations varied by obesity status, smoking status, physical activity level, history of hypertension, and genetic variants previously ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…Except our previous study with a smaller sample size which reported a non-statistically significant protective effect on renal cell carcinoma20, there has been no other studies on the “Tex-Mex” dietary pattern and cancer. The mechanism(s) linking high adherence to the “Tex-Mex” pattern with a decreased risk of lung cancer is unclear.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Except our previous study with a smaller sample size which reported a non-statistically significant protective effect on renal cell carcinoma20, there has been no other studies on the “Tex-Mex” dietary pattern and cancer. The mechanism(s) linking high adherence to the “Tex-Mex” pattern with a decreased risk of lung cancer is unclear.…”
Section: Discussionmentioning
confidence: 55%
“…The number of factors that best represented the data was chosen on the basis of eigenvalues greater than one, identification of a break point in the scree plot, interpretability, and our previous dietary pattern analysis on renal cell carcinoma20. We identified three factors that best represented the dietary input data, and these three dietary patterns were identical to the three patterns identified in our previous study of renal cell carcinoma20. The final analysis was restricted only to the three chosen factors.…”
Section: Methodsmentioning
confidence: 99%
“…The Tex‐Mex pattern is based on an American regional cuisine which is quite specific for the area where our study was conducted. Except for two studies on renal cancer risk and lung cancer risk, no studies reported about this pattern before. The Tex‐Mex pattern contains potentially beneficial components such as legumes, as well as potentially harmful components such as red meat and pizza.…”
Section: Discussionmentioning
confidence: 99%
“…A cut-off was defined at the 75th percentile plus 1.5 times the interquartile range (3553.3 kcal) and the 25th percentile minus 1.5 times the interquartile range (190.9 kcal) [27]. This led to the exclusion of two FFQs with an over-reporting of energy intake (4250.3 kcal, 5414.3 kcal).…”
Section: Methodsmentioning
confidence: 99%